SISTEM INFORMASI GEOGRAFIS UMKM BAHAN MAKANAN DAN PANGAN BAGI MASYARAKAT DALAM MENGHADAPI NEW NORMAL - Achmad, Andini Dani; Arief, Abdul Samad; Din, Diel; Rusli, Muh. Dzulfadli; Rajib, Farhan Muhammad (STMIK Palangkaraya, 2022)
This study aims to build a web-based geographic information system for food material and foodstuffs UMKMs in Makassar City to disseminate geographic information that can be accessed anytime and from anywhere. The system is designed using a sequential waterfall method. Data sourced from the Makassar City Cooperatives and UKMs Office, field surveys, and interviews with UMKM owners. This system were developed to assist the government in providing information to the public about the location and distribution of UMKMs and other related information in dealing with the new normal, because it can visualize the distribution in Makassar City well. The system has been successfully developed through public testing, the average values ​​of which are user objectives (4.18), information quality (4.13), and System Quality (4.12).